Applying sustainability principles in the economy - Grundey, Dainora (Technological and Economic Development of Economy, 2008)
Editorial “Applying sustainability principles in the economy” Technological and Economic Development of Economy, 14(2), 101–106. Guest Editor Prof. Dainora Grundey First published online: 21 oct 2010